ISLAM & AKTIVITAS PASAR DALAM PERSPEKTIF EKONOMI SYARIAH - Desky, Harjoni (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
This  article  aims  to  explain  the  nature  of  the  market mechanism in Islamic economic thought and its practice. Historical  and  philosophical  approach  are  used  in  this article to explore the ideas and insights of Muslim scholars on  the  market.  The  article  concludes  that  within  the framework  of  Islam,  the  market  mechanism  has  been considered  as  an  important  part  of  economic  activity. According  to  Islamic  economy,  market  mechanism  can occur  naturally  on  the  side  of  supply  and  demand  as  it should  be.  Furthermore,  within  the  mechanism  of  the market  economy  perspective  of  Islam,  its  principle  is  to reject  the  existence  of  an  intervention  price  if  the  price changes  occur  due  to  normal  market  mechanisms. However, the market here requires morality, such as: fair competition,  honesty,  transparency,  and  justice.  If  these values have been established, there is no reason to reject the market price. And if there are deviations, the obligation of the state to regulate it for the benefit of the people.